Design and fabrication of structural color by local surface plasmonic meta-molecules*Project partially supported by the National Natural Science Foundation of China (Grant No. 61205148). (August 2015) - Ma, Ya-Qi; Shao, Jin-Hai; Zhang, Ya-Feng; Lu, Bing-Rui; Zhang, Si-Chao; Sun, Yan; Qu, Xin-Ping; Chen, Yi-Fang
Abstract In this paper, we propose a new form of nanostructures with Al film deposited on a patterned dielectric material for generating structural color, which is induced by local surface plasmonic resonant (LSPR) absorption in sub-wavelength-indented hole/ring arrays. Unlike other reported results obtained by using focus ion beam (FIB) to create metallic nanostructures, the nano-sized hole/ring arrays in Al film in this work are replicated by high resolution electron beam lithography (EBL) combined with self-aligned metallization. Clear structural color is observed and systematically studied by numerical simulations as well as optical characterizations. The central color is strongly related to the geometric size, which provides us with good opportunities to dye the colorless Al surface by controlling the hole/ring dimensions (both diameter and radius), and to open up broad applications in display, jewelry decoration, green production of packing papers, security code, and counterfeits prevention.